Avaliação da atividade fotodinâmica frente a agentes de micoses cutâneas e subcutâneas - Keller, Jéssica Tairine (2018)
Cutaneous and subcutaneous mycoses affect both immunocompeten individuals and immunocompromised individuals. Generally prolonged therapeutic treatments and, recurrences during treatment are quite common. Scopulariopsis brevicaulis is an agent of cutaneous mycoses, mainly onychomycosis. Fonsecaea pedrosoi and Scedosporium apiospermum are agents of chromoblastomycosis and mycetomas, respectively. These fungal agents are resistant to most of the conventional antifungal agents used in the treatments. Photodynamic therapy emerges as an alternative to the treatment of these localized skin infections, combining three factors: photosensitizer, visible light and oxygen. Photosensitizer activation results in the production of reactive oxygen species that in a sequence of photochemical and photobiological reactions generates the inactivation of the target cell. In this study the photodynamic activity on S. brevicaulis, F. pedrosoi and S. apiospermum was evaluated, using phenothiazine photosensitizers and a diode laser (InGaAlP). The results demonstrated that the photodynamic activity was evidenced against S. brevicaulis and S. apiospermum, when methylene blue was used as a photosensitizer. On the other hand, when toluidine blue was used as a photosensitizer, the three fungal agents tested showed sensitivity to photodynamic activity. Methylene blue and toluidine blue are chemically dye of the phenothiazines group, and function as cationic phenothiazine photosensitizers, being very efficient in the production of singlet oxygen. In addition, they have a good interaction with the wall and the fungal plasma membrane. The results of this study suggest that photodynamic therapy may be a very promising treatment alternative, however, clinical studies carefully conducted need to be developed.